SPONTANEOUS ADVERSE DRUG REACTION REPORTS FOR TRANSPLACENTAL AND TRANSMAMMARY ROUTES IN THOSE ≤1 YEAR IN THE UK 2001–2010. Issue 1 (14th December 2015) - Russell, Nicki-Jayne; Turner, Mark; Hawcutt, Dan
Abstract : Aims: The UK Medicines and Healthcare products Regulatory Agency (MHRA) runs a national spontaneous reporting system (Yellow Card Scheme, YCS) to collect suspected adverse drug reaction (ADR) data. We describe the Yellow card reports received for patients aged ≤1 year across a 10 year period (2001–10). Methods: The MHRA supplied YCS data for patients aged ≤1 year from the years 2001–2010. This analysis includes all reports involving transplacental, transmammary, or paternal route of exposure. Data were analysed to include number, type and outcome of ADRs. Results: There were 279 reports, including 249 different medications (a YCS may contain ≥1 medication). The most commonly reported drugs were fluoxetine (n=25), citalopram (n=22), paroxetine (n=19) and venlafaxine (n=19). The outcome of the ADR was death in 10.4% of reports. Doctors reported 75.4% (n=215) of reports, however only 3.9% (n=11) were from the parent/carer. Gender was documented in 66% cases and gestation was stated in only 15% of reports. Conclusions: Despite many women requiring medications in pregnancy and while lactating, very few YCS reports were received over a 10 year period. Current MHRA advice is for all suspected ADRs in children following transplacental or transmammary exposure to be reported. Strategies to improve reporting in this neglected population are urgently needed.